Pengaruh Tanaman Penutup Tanah Jenis Mucuna bracteata Terhadap Sifat Fisika Tanah Pada Beberapa Kelas Kemiringan Lahan di Perkebunan Kelapa Sawit PTPN XIII Kecamatan Meliau - Harahap, Asrul Sigama; Dr. Ir. Urai Edi Suryadi, MP, Dr. Ir. Urai Edi Suryadi, MP; Ir. Junaidi, MP, Ir. Junaidi, MP (Fakultas Pertanian Universitas Tanjungpura, 2016)
Cover crop Mucuna bracteata type have important functions in maintaining and improving the quality of soil physical properties , particularly in the area called the land slopes. This study was conducted to determine the effect of cover crops or Legume Cover Corp types of Mucuna bracteata the physic properties of the soil at different levels of the slope in the oil palm plantation PTPN XIII District of Meliau. Sampling was done by random sampling on the ground with a slope flatland, moderately steep and steep .The studies conducted physics properties parameters that are bulk density , porosity , field capacity moisture content, permeability and soil aggregate stability and chemical properties is organic matter content , total nitrogen content and C/N ratio in the soil. Research results showed the soil with a moderately steep and steep has a high bulk density. On land with a flatland, moderately steep and steep has poorly porosity .Based on statistical analysis, field capacity moisture content each slope experiencing a significant effect. The highest permeability soil is moderately steep. At soil aggregate stability slope classes flatland, moderately steep, and steep has a massive aggregate stability The Very steady. As for the chemical properties of soil organic matter which medium content, low nitrogen content, and the C/N ratio is low on the ground with a slope flatland, rather steep and steep.